The relationship between personality traits, values and interests in adolescents - Mihaela Luminița Sandu; Mihaela Rus; Tănase Tasențe (Technium Social Sciences Journal, 2020)
Choosing this theme study was based on a desire to investigate several issues in depth, taking into account the importance of identifying dimensions of personality structure in adolescence, considering that during this period proper development of adolescents is based on stimulating several areas closely related to their activity. A balanced adolescent chooses activities that contribute to character development, increasing self-confidence, developing socializing skills, identifying passions and making decisions.